2001
DOI: 10.1021/ja0033178
|View full text |Cite
|
Sign up to set email alerts
|

Gemini Surfactants with a Disaccharide Spacer

Abstract: A gemini surfactant is an amphiphile possessing (in sequence) the following: hydrocarbon tail/polar group/spacer/polar group/hydrocarbon tail. Widespread interest in geminis has emerged recently from both industrial and academic laboratories. In the present contribution, two related families of geminis have been synthesized, both with trehalose, a disaccharide, as a polar spacer. One family, Series-A, is nonionic and has amide groups separating the long chains from the trehalose spacer. The other family, Serie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
104
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(108 citation statements)
references
References 39 publications
3
104
0
1
Order By: Relevance
“…The mixture of conventional/Gemini Surfactants would exhibit the synergism in the decline of surface tension and the formation of mixed micelles. 15 At the end of the reaction, the conversion of the monomer reached to 95% (determined gravimetrically in an independent experiment), which was consistent with , which suggested that almost all the monomer had participated in the reaction and there was no C¼ ¼C bonds left in the system. The characteristic peaks of PDMS were similar with that of MPS-PDMS oligomer.…”
Section: Ftir Spectrumsupporting
confidence: 76%
See 1 more Smart Citation
“…The mixture of conventional/Gemini Surfactants would exhibit the synergism in the decline of surface tension and the formation of mixed micelles. 15 At the end of the reaction, the conversion of the monomer reached to 95% (determined gravimetrically in an independent experiment), which was consistent with , which suggested that almost all the monomer had participated in the reaction and there was no C¼ ¼C bonds left in the system. The characteristic peaks of PDMS were similar with that of MPS-PDMS oligomer.…”
Section: Ftir Spectrumsupporting
confidence: 76%
“…First, the critical micelle concentration (CMC) values of Gemini surfactants lower one to two orders of magnitude than that of corresponding single-chain surfactants. 15 Second, they are much more efficient than their corresponding monomeric surfactants in decreasing the surface tension of water. 16 For example, the C20 (surfactant concentration required for lowering the surface tension of water by 20 mN/m) for 12-2-12 Gemini is 0.0083 wt %, whereas that for C12TAB is 0.25 wt % 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Over the last two decades, the growing demand for highperformance surface-active agents has multiplied the interest of the academic and industrial communities for the development of new gemini surfactants [1][2][3][4][5] . Their identical amphiphilic moieties connected by a spacer group impart them unique surface-active properties and selfassembly patterns, and also play a significant role in their antimicrobial performances 6,7) .…”
Section: Introductionmentioning
confidence: 99%
“…With the aid of a Langmuir film balance, surfactant monolayers were slowly compressed by a moveable barrier and the isotherms recorded. The resulting "surface pressuremolecular area isotherms" provide insight into the packing behavior of the surfactant molecules within the monolayers [16]. Fig.…”
Section: The Monolayer Behavior Of 2m-s-2m On the Air/water Interfacementioning
confidence: 99%